Pengendalian Kerusakan Lingkungan Akibat Aktivitas Pertambangan di Kecamatan Pasir Sakti - Feri Andriawan; Muhammad Akib; Agus Triono (Penerbit Goodwood, 2021)
Purpose: This study aims to determine whether sand mining activities in Pasir Sakti District cause environmental damage and directly impact the community's life sector. There are over 1000 hectares of abandoned mining areas. The researcher is interested in examining problems, in this case, how efforts to control environmental damage caused by sand mining activities are progressing and what factors are impeding the implementation of environmental damage control. Research Methodology: This research takes an empirical normative approach to the problem. This is accomplished by describing and analyzing the results obtained from library data and field observations. Results: The findings indicated that a variety made efforts to implement control of parties, including the Environmental Service, the Police, and the community. Socialization of the community is needed in order to deter illegal mining and the resulting environmental damage. As a countermeasure, the imposition of administrative sanctions in government coercion through the control of illegal mining activities. Additionally, community involvement in rehabilitating and reforesting former mining areas contributes to recovery should be imposed. These parties' environmental damage control efforts have been less than optimal due to impeding factors such as a lack of institutional coordination or cooperation among the parties responsible for implementing the control and the absence of strict sanctions against illegal sand miners Contribution: The author proposes a review of existing control programs and increased enforcement efforts against illegal sand miners.